Interleukin (IL)-21 Promotes the Differentiation of IgA-Producing Plasma Cells in Porcine Peyer's Patches via the JAK-STAT Signaling Pathway - Liu, Guo; Wang, Bin; Chen, Qingbo; Li, Yang; Li, Baoyu; Yang, Ning; Yang, Shanshan; Geng, Shuxian; Liu, Guangliang (Frontiers in Immunology, 2020)
Secretory IgA is critical to prevent the invasion of pathogens via mucosa. However, the key factors and the mechanisms of IgA generation in the porcine gut are not well understood. In this study, a panel of factors, including BAFF, APRIL, CD40L, TGF-β1, IL-6, IL-10, IL-17A, and IL-21, were employed to stimulate IgM+ B lymphocytes from porcine ileum Peyer’s patches. The results showed that IL-21 significantly upregulated IgA production of B cells and facilitated cell proliferation and differentiation of antibody-secreting cells. In addition, three transcripts in porcine IgA class switch recombination (CSR), germ-line transcript α, post-switch transcript α, and circle transcript α, were first amplified by (nest-)PCR and sequenced. All these key indicators of IgA CSR were upregulated by IL-21 treatment. Furthermore, we found that IL-21 predominantly activated JAK1, STAT1, and STAT3 proteins and confirmed that the JAK-STAT signaling pathway was involved in porcine IgA CSR. Thus, IL-21 plays an important role in the proliferation and differentiation of IgA-secreting cells in porcine Peyer’s patches through the JAK-STAT signaling pathway. These findings provide insights into the mucosal vaccine design by regulation of IL-21 for the prevention and control of enteric pathogens in the pig industry.